Strategi UKM dalam Pengembangan Industri Maritim di Indonesia: (Studi pada Industri Kecil Pengolahan Ikan Cakalang Fufu di Kota Bitung Sulawesi Utara) - Jaclin Sumual; Yantje Uhing; Christoffel Mintardjo (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2022)
Fish processing activities in Indonesia are still classified as traditional fish processing and are carried out on a home industrial scale. Processing of fishery products in Bitung City is a small-scale traditional processing industry (home industry). This research aims to produce strategies/policies/methods to develop SMEs based on fish processing in Bitung City. The research method used is a case study on SMEs Processing Cakalang Fufu in Bitung City. The analytical method used is qualitative and quantitative analysis methods, namely SWOT analysis with weighting. The findings reveal the strategy of fish processing SMEs in the development of the maritime industry in Indonesia.